Generation of gigawatt 10-GHz pulses with stable phase; Technical Physics Letters; Vol. 34, № 10 - Grishin D. M.; Lyubutin S. K.; Mesyats G. A. Gennady Andreyevich; Rostov V. V.; Rukin S. N.; Slovikovsky B. G.; Timoshenkov S. P.; Ul'maskulov M. R.; Sharypov K. A.; Shpak V. G.; Shunailov S. A.; Yalandin M. I. (2008, 2008)
В фонде НТБ ТПУ отсутствует